Dicarba-nido-undecaborates: topological analysis - S. P. Knyazev; E. G. Gordeev; A. Yu. Kostyukovitch; A. Yu. Shkulipa (Тонкие химические технологии, 2011)
Calculations of parameters of function of full electron density in molecules of dicarba-nido-undecaborates were carried out by the first order Promega method using MP2(full)/6-311++G(2d,p) level of theory. The features of electron structure of undecaborates and the relation of parameters of function of full electron density with their chemical properties were revealed.